The Constant Listener : Henry James and Theodora Bosanquet--An Imagined Memoir. - Sibbet, Susan Herron (Ohio University Press, 2017)
In 1907, in a quiet English village, Theodora Bosanquet answered Henry James's call for someone to transcribe his edits and additions to his formidable body of work. The aging James had agreed to revise his novels and tales into the twenty-four-volume New York Edition.